Effect of Different Tillage Options and Residue Retention for Sustainable Crop Production in Wheatmungbean- Rice Cropping Pattern in Dry Areas - Hossain, MI; Hossain, MI; Ohab, MA; Sheikh, MHR; Nag, BL (Bangladesh Agronomy Journal, 2020)
The study was conducted to know the productivity and soil fertility status of intensified rice-wheat (RW) systems by adding a third pre-rice crop mungbeani.ewheat-mungbeanrice cropping pattern. The trial comprises five packages of practices including crop residue retention, seeding methods with tillage options imposed on the component crops in the same cropping pattern. The results indicated that keeping standing 30% crop residue in the field with minimum disturbance of soil had significant contribution on grain yield of wheat-mungbean-rice sequence compare to conventional practice of well-till without crop residue retention. System productivity and fertility were evaluated under five levels of tillage options (zero, strip, raised bed, minimum tillage by power tiller operated system (PTOS) and conventional tillage practice (CTP) in a RWM cropping pattern. Both permanent raised bed and strip till with 30% straw retention produced the highest productivity in all years and the lowest yield was also found from conventional practice with 30% straw retention.Soil organic matter in surface soil had increased by 0.12% after 3years crop cycles with 30% SR from rice and wheat and full residue retention from mungbean crop. Straw retention is an important component of soil management and may have long term positive impacts on soil quality. The combination of raised bedsystems and strip tillage with 30% residues retained appears to be a very promising technology for sustainable intensification of wheat-mungbean-rice croppingpattern in dry zone areas. Bangladesh Agron. J. 2019, 22(2): 67-75